1984
DOI: 10.1080/00362178485380471
|View full text |Cite
|
Sign up to set email alerts
|

Muscle invasion byBasidiobolus haptosporus

Abstract: Invasion of muscle tissue in addition to dermis and subcutaneous tissue by Basidiobolus haptosporus is reported in a 40-year-old female housewife. This infection followed intramuscular injection injury of the right gluteal region. Oral KI cured the condition completely in 6 months. Intramuscular implantation of B. haptosporus by the injection needle is the probable mode of infection in this case. Possible blood vessel invasion seen in histology suggests the possibility of dissemination of the fungus.Basidiobol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 5 publications
0
34
1
Order By: Relevance
“…Three of the five infected patients died due to progression and obstruction. Basidiobolus has also been identified in patients with lymph node (224,225,228) and muscle (227,228) involvement. Other reports of invasive disease with B. ranarum include a case of invasive retroperitoneal infection in an 8-year-old boy (320) and a patient with locally aggressive disease originating in the maxillary sinuses causing ulcerations in the hard palate (133).…”
Section: Entomophthorales Causing Zygomycosis In Humansmentioning
confidence: 95%
See 3 more Smart Citations
“…Three of the five infected patients died due to progression and obstruction. Basidiobolus has also been identified in patients with lymph node (224,225,228) and muscle (227,228) involvement. Other reports of invasive disease with B. ranarum include a case of invasive retroperitoneal infection in an 8-year-old boy (320) and a patient with locally aggressive disease originating in the maxillary sinuses causing ulcerations in the hard palate (133).…”
Section: Entomophthorales Causing Zygomycosis In Humansmentioning
confidence: 95%
“…In addition to subcutaneous infection, basidiobolomycosis has expanded to involve other tissues including the gastrointestinal tract, lymph nodes, and muscles (41,110,225,228,320,359). Angioinvasive disease has also been seen in one culture-confirmed case (228).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Iatrogenic infection has been reported. Nazir et al (1997) reported a case of possible inoculation during appendectomy, and Kamalam & Thambiah (1984) reported inoculation from a needle injection. B. ranarum typically causes a chronic infection of the peripheral or subcutaneous tissue, usually on the arms, trunk and buttocks (Goodman & Rinaldi, 1991).…”
Section: Introductionmentioning
confidence: 99%